Spatial Patterns in Late Holocene Lithic Projectile Point Technology of Tierra del Fuego (Southern South America): Assessing Size and Shape Changes - Charlin, Judith Emilce (2014)
This paper focuses on the application of geometric morphometrics to the study of the lithic record in southern South America. We review the regional background, discuss methodological issues, and summarize research advances. Here a geometric morphometric approach is applied to the case study of Late Holocene stemmed lithic projectile points from Grande Island of Tierra del Fuego (southernmost South America). Our aim is to assess size and shape changes in a broad spatial scale. Projectile point morphometric variations are used to discuss spatial scales of interaction and differentiation among past human populations across the island. Finally, several hypotheses are introduced to explain the patterns observed.